Analisis Value Chain dalam Mengakomodasi Preferensi Wisatawan Gen-Z di Desa Wisata Budaya Dokan - Nova Bernedeta Sitorus; Shofia Hamida Hasibuan; Miladdia Putri; Nurhafizhah Khairi; Febryola Indra (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
This study aims to analyze the tourism value chain in accommodating Generation Z tourist preferences in Desa Wisata Budaya Dokan. The research employed a mixed-method approach combining qualitative and quantitative methods through Conjoint Analysis. Data were collected using questionnaires, in-depth interviews, observation, and documentation involving 100 Gen-Z tourists selected through purposive sampling. The findings reveal that cultural aspects are the primary motivation for tourists, reflected by the highest utility value, while public facilities received negative utility scores, indicating weaknesses in basic tourism services. Facilities emerged as the most important attribute influencing travel decisions among Gen-Z tourists. Furthermore, the value chain analysis indicates that tourism management in Dokan Village remains fragmented and insufficiently integrated, particularly in terms of facilities, digital marketing, institutional support, and local economic value creation. Therefore, strengthening the tourism value chain through authentic cultural experiences, improved facilities, and digital promotion strategies aligned with Gen-Z characteristics is essential to enhance destination competitiveness and sustainability.